Best bilinear approximations of functions from Nikolskii-Besov classes - Romanyuk, A. S.; Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain exact-order estimates for the best bilinear approximations of Nikol'skii-Besov classes in the spaces of functions $L_q (π_{2d})$.